Asimilasi Suku Jawa dan Suku Tamil di Sei Serayu Gang Buntu, Kecamatan Medan Sunggal Sumatera Utara - Mardiana Lestary; Rehia K. Isabella Barus; Armansyah Matondang (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2020)
The purpose of this study was to find out interpersonal communication in the assimilation of the Javanese and Tamil Groups in the dead alley, to find out the assimilation of Javanese tribes and Tamil tibes in Sei Serayu Buntu Alley, Medan Sunggal sub-district, North Sumatera, and to find out what factors were the barriers and supporters of the assimilation of Javanese and Tamil tribes. This study uses the assimilation theory. In collecting data, research conducted face to face interviews with four informants, including two Tamil informants, and two Javanese informants. This study uses skinative research with descriptive analysis. The results of this study are that there is a mixed marriage between the Javanese and Tamil tribes as well as a factor of tolerance and cultural similarity between the two tribes.